Microbial biomass carbon in soil cultivated with soybean, under different management systems in Cerrado - Perez, Kátia Sueli Sivek; Ramos, Maria Lucrécia Gerosa; McManus, Concepta (Pesquisa Agropecuaria Brasileira, 2004)
The aim of this study was to quantify soil microbial biomass carbon in a soybean crop under different soil management systems: no-tillage, single harrowing, subsoiling and two harrowing, on a clay Red-Yellow Latossol in the Cerrado region. Soils were studied at five depths: 0–5, 5–10, 10–20, 20–30 and 30–40 cm. Four periods were observed: before soil preparation; 30 days after germination; flowering stage and after harvesting soybean plants. The same measurements were taken under the same conditions in an area of native cerrado vegetation, adjacent to the experiment (Cerrado sensu strictu). Subsoiling showed highest carbon values 30 days after germination (865.7 mg kg-1 of soil). This was reduced to less than 10% (80.3 mg kg-1) at flowering. The carbon values were more stable in the no-tillage system, mainly in the 0–20 cm layer. The layers 0–5 cm and 5–10 cm showed significantly higher carbon values compared with other layers in most of the studied periods and depths. Subsoiling showed the lowest soil organic carbon level after soybean harvesting. Only in the system with subsoiling there was no significant correlation between the microbial carbon:organic carbon index and soil nutrients.